Èsquil al Curial e Güelfa. - REDONDO, JORDI (Scripta, 2018)
The third book of the pre-Renaissance novel Curial e Güelfa shows the features of a prose deeply indebted with Humanism. Noteworthy elements of this influence are the mythological discourse, the setting of a huge part of the events, and the imitation of Classical literary models. In this paper we aim to elucidate to what a extent, if there was such an imitation, the Aeschylean tragedy in which was put on stage the trial of Orestes, the Eumenides, could become the literary model for the trial of Curial at the Parnasse, as was some years ago suggested by Patricia Boehne. After different methodological premises from her's, we base our conclusions on the intertextual relations established between both texts.